Using Science and Technology Intelligence to Drive Business Results - American Productivity & Quality Center; American Productivity & Quality Center (APQC American Productivity & Quality Center, 2001)
Learn about the role of intelligence, processes for organization, storing and distributing intelligence, and measuring success in Using Science and Technology Intelligence To Drive Business Results.